Analisis Posisi Komoditas Jahe Indonesia di Pasar Internasional - Novia Ely Mazzlin; Sri Widayanti; Sigit Dwi Nugroho (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
Indonesia ranks fifth for the world’s most significant ginger production in 2020 after India, Nigeria, China, and Nepal. However, this does not make Indonesia a major ginger exporter in the international market. This study analyzes the position of Indonesian ginger in the global market compared to its competitors based on comparative advantage, competitive advantage, and trade specialization. The research methods used Revealed Comparative Trade Advantage (RTCA), Export Competitiveness Index (XCi), and Trade Specialization Index (ISP). The data used in this study is secondary data for the period 2006-2020 obtained from the Food and Agriculture Organization (FAO) with item code 720 (ginger), which consist of the export and import value of ginger from the country concerned, the export and import value of world ginger, and also the export and import value of all goods from the country affected. The result showed that the Indonesian ginger commodity has comparative competitiveness, competitive competitiveness, and trade specialization as an exporter of ginger in the international market. RCTA analysis shows an average value of 0,538, making Indonesia the country with the lowest comparative competitiveness among other competitors. XCi analysis indicates that Indonesia has the highest competitive competitiveness compared to its competitors, with an average value of 1,351. ISP analysis shows that Indonesia tends to be an exporter of ginger with an average value of 0,29 and is in the growth stage. Indonesia has the potential to develop the competitiveness of ginger exports in the international market by optimizing the utilization of existing resources and improving the quality of ginger. The competition for ginger exports in the global market is currently very tight, so for further research, it is recommended to analyze non-traditional markets that can be used as a potential to develop the Indonesian ginger export market.